1966
DOI: 10.1111/j.1748-5827.1966.tb04388.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermoid Sinus in the Rhodesian Ridgeback

Abstract: Abstract—The Rhodesian Ridgeback is a modern breed having been standardized in 1922. It originated in South Africa by crossing Hottentot dogs with various European breeds. The breed has one defect, a congenital malformation, generally known as dermoid sinus. The authors have investigated the inheritance of the condition and, contrary to the hypotheses of others, suggest that it is a simple recessive character. The implications of this are discussed. Réslamé—Le chien de Rhodesie, dénommé Ridgeback, est d'un éle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 2 publications
2
63
0
2
Order By: Relevance
“…There are many reports in Rhodesian ridgebacks (Mann & Stratton 1996) but a dermoid sinus has been reported only once previously in a shih‐tzu (Selcer and others 1984). Reports have shown that neurological signs with dermoid sinuses are most often caused by infection of the sinus with dissemination to the spinal cord or brain (that is, myelitis, encephalitis).…”
mentioning
confidence: 99%
“…There are many reports in Rhodesian ridgebacks (Mann & Stratton 1996) but a dermoid sinus has been reported only once previously in a shih‐tzu (Selcer and others 1984). Reports have shown that neurological signs with dermoid sinuses are most often caused by infection of the sinus with dissemination to the spinal cord or brain (that is, myelitis, encephalitis).…”
mentioning
confidence: 99%
“…In the veterinary literature, there are only two other studies that described true cutaneous dermoid cysts (DS type V) in dogs [11,26] and neither of them were of subtype b. Our case is also unusual for its presentation on the head, for the breed affected and the multiplicity of the lesions, a pattern rarely described in dogs or humans [6,14,16,19]. DS is reported as a congenital or acquired lesion [3,6,41].…”
Section: Discussionmentioning
confidence: 65%
“…However, some authors recently proposed that a distinction should be made in dogs and cats, as it is done in humans, between dermoid cysts and DSes based on the presence in the latter of a connection to the skin [4,27,56,57]. Similarly, other authors identified different types of DS in dogs and considered dermoid cyst as a specific type of DS lacking an opening on the skin [19,26,35,55]. Based on the extent of penetration into the subcutaneous tissue, four types of DSes were initially recognized in veterinary medicine: type I extends ventrally as a cylindrical sac attached to the supraspinous ligament, type II consists of a sac-like portion that is more superficial than that of type I and is attached to the ligament by a fibrous band, type III is made up of a superficial sac with no attachment to the supraspinous ligament and type IV extends to the spinal canal and is attached to the dura mater [19].…”
Section: Discussionmentioning
confidence: 99%
“…Dermoid sinus is generally benign: it occurs at the dorsal midline and connects the skin to deeper spinal structures, including the vertebral canal [1-4]. Spinal dermoid sinus occur as single or multiple lesions in the cervical, cranial thoracic, thoracolumbar, lumbosacral, and sacrococcygeal regions [5-9].…”
Section: Introductionmentioning
confidence: 99%
“…There are six types of dermoid sinus described in veterinary medicine categorized by the relationship between the sinus and supraspinous ligament, and the presence of a skin orifice (Figure 1) [4,6,7,10]. Type I dermoid sinus is a tubular sac extending from the skin to the supraspinous or nuchal ligament.…”
Section: Introductionmentioning
confidence: 99%